A survey on control for Takagi-Sugeno fuzzy systems subject to engineering-oriented complexities. Issue 1 (1st January 2021) - Wang, Yezheng; Zou, Lei; Ma, Lifeng; Zhao, Zhongyi; Guo, Jiyue
Abstract : Nonlinearities exist everywhere and the investigation on control problems for nonlinear systems is of both theoretical and practical significance. The Takagi-Sugeno (T-S) fuzzy techniques, as one of the powerful model-based tools for dealing with control problems for nonlinear systems, have received considerable and persistent research attention during the recent decades. Based on the T-S fuzzy model, many complicated nonlinear control problems have been addressed in the literature. In this paper, we aim to provide a survey with respect to the T-S fuzzy control problems with complexities that are frequently encountered in the engineering practice. Firstly, the backgrounds of the fuzzy control and engineering-oriented complexities are discussed. The considered complexities are divided into traditional engineering-oriented ones and the network-induced ones. The former mainly includes time-delays, parameter uncertainties, sensor/actuator faults and the latter contains network-induced phenomena, communication protocols, event-triggered schemes and cyber-attacks. Then, the recent progress on the T-S fuzzy control problems subject to these complexities has been reviewed in details. Finally, based on the literature review, the conclusions are drawn and some possible future topics are given.